PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING (PBL) BERBANTUAN APLIKASI CANVA PADA MATERI PERUBAHAN LINGKUNGAN KELAS X DI SMA NEGERI 1 TELAGA BIRU - Alisa H. Kadir, Nur; Mardin, Herinda; M. Hasan, Ani; Wahyuni K. Baderan, Dewi; Nusantari, Elya; S. Hamidun, Marini; H. Husain, Ilyas (Jurnal Biogenerasi, 2024)
This research aimed to discover and describe E-Modules development based on Problem-Based Learning (PBL) assisted by the Canva application to improve student learning outcomes in Class X of SMA (Senior High School). This research used the Research & Development (R&D) method with a model ADDIE, which was carried out in a limited trial on 20 students in class X-5 in SMA Negeri 1 Telaga Biru. The study's findings indicated that (1) the media validation test obtained a score of 76% (Valid), and the material validation test's score was 87% (Very Valid). (2) The Practicality Test consisted of a teacher response test that obtained a score of 87% (Very Practical), and student responses obtained a score of 93% (Very Practical). (3) Students' learning outcomes through a Pretest- Posttest evaluation, based on the N-Gain scale, obtained a score of 0.60 (Moderate) or 60% (Fairly Effective).